Investigation of Optimal Pedagogical Approaches for Generation Z to Develop a High-Caliber Generation - Surya Atmaja; Ibnu Khalid (Enigma Institute, 2023)
Generation Z is a generation that was raised with the convenient availability of technology devices, including smartphones, tablets, and computers. They are familiar with digital settings and strongly enjoy using technology in the teaching and learning process. Hence, conventional educational approaches that were successful in the past may not adequately meet the needs of Generation Z, who is enthusiastic about embracing a more interconnected and technologically advanced society. The literature search was conducted across multiple databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) to identify the most efficacious educational approaches for generation Z, with the aim of fostering the development of individuals of high caliber. Granting students autonomy in both subject matter and instructional methods enhances their motivation and involvement. The differentiation learning paradigm enables students to access content that aligns with their individual interests and aptitudes. Engaging in the resolution of practical issues fosters the development of problem-solving and critical thinking abilities. Utilizing cooperation and interaction in both in-person and virtual learning environments aids in the cultivation of social and collaborative abilities for generation Z. Aside from academic content, it is crucial to impart soft skills, such as proficient communication, creativity, problem-solving, and critical thinking abilities, to equip individuals to confront practical obstacles. An effective education for generation Z necessitates the integration of these components to establish a learning atmosphere that is pertinent, inspiring, and equips them for triumph in a constantly evolving world. Thus, generation Z can cultivate the essential aptitudes and evolve into individuals who are well-equipped to confront forthcoming obstacles.